Dismiss Notice
Join Physics Forums Today!
The friendliest, high quality science and math community on the planet! Everyone who loves science is here!

Forced equations

  1. Nov 29, 2009 #1
    I need to compute the general solution to:

    y'' + 2y' = 3t+2

    The only method we have been taught is to first find the general solution of the unforced equation and then find the particular solution.

    For general solution, the characteristic polynomial is L^2 + 2L = 0 (where L= lambda)

    L^2 = -2L
    L = -2

    So general solution of unforced equation is y(t) = k1e^-2t +K2te^-2t

    I am fairly certain about the above. The particular solution is a bit trickier for me.

    guess: yp(t) = At + b

    Plug in: 2A = 3t + 2
    A = (3/2)t + 1

    Is that correct? It seems like an odd answer, and B sort of just disappeared.
     
  2. jcsd
  3. Nov 29, 2009 #2

    LCKurtz

    User Avatar
    Science Advisor
    Homework Helper
    Gold Member

    Don't forget that the general solution to the NH equation consists of the general solution to the homogeneous equation plus a particular solution to the NH equation.
     
  4. Nov 29, 2009 #3

    HallsofIvy

    User Avatar
    Staff Emeritus
    Science Advisor

    Well, no. You get L= -2 if you divide by L which you cannot do if L= 0. The two roots are L= -2 and L= 0.

    No, the general solution to the unforced equation is [itex]y(t)= k_1e^{-2t}+ K_2e^{0t}[/itex][itex]= k_1e^{-2t}+ K_2[/itex].

    No that is not correct. The whole point of writing "y= At+ B" is that A and B are to be constants. A cannot be "(3/2)t+ 1" so your particular solution is NOT "(3/2)t^2+ 2t".

    If you set y= At+ B, then y'= A and y"= B. That means your equation becomes y"+ 2y'= 0+ B= 3t+ 2. That's impossible because we have no "t" on the left. The problem is that the "3t+ 2" correspond to multiples of [itex]e^{0t}= 1[/itex] which is already a solution to the associated homogeneous equation. Just like with a multiple root, you should try multiplying by "t". If [itex]y(t)= At^2+ Bt[/itex], then [itex]y'= 2At+ B[/itex] and [itex]y"= 2A[/itex]. Now the equation becomes [itex]y"+ 2y= 2A+ 4At+ 2B= 4At+ (2A+ 2B)= 2t+ 3[/itex]. For that to be true for all t, we must have 4A= 2 and 2A+ 2B= 3. From the first equation, A= 1/2. Then the second equation becomes 1+ 2B= 3 so B= 1.

    Now, write down the specific solution and the general solution to the entire equation.
     
Know someone interested in this topic? Share this thread via Reddit, Google+, Twitter, or Facebook